The Anatomy of Post-Communist Regimes A Conceptual Framework - Magyar, Bálint (2020)
Offering a single, coherent framework of the political, economic, and social phenomena that characterize post-communist regimes, this is the most comprehensive work on the subject to date. Focusing on Central Europe, the post-Soviet countries and China, the study provides a systematic mapping of possible post-communist trajectories. At exploring the structural foundations of post-communist regime development, the work discusses the types of state, with an emphasis on informality and patronalism; the variety of actors in the political, economic, and communal spheres; the ways autocrats neutralize media, elections, etc. The analysis embraces the color revolutions of civil resistance (as in Georgia and in Ukraine) and the defensive mechanisms of democracy and autocracy; the evolution of corruption and the workings of "relational economy"; an analysis of China as "market-exploiting dictatorship"; the sociology of "clientage society"; and the instrumental use of ideology, with an emphasis on populism. Beyond a cataloguing of phenomena-actors, institutions, and dynamics of post-communist democracies, autocracies, and dictatorships-Magyar and Madlovics also conceptualize everything as building blocks to a larger, coherent structure: a new language for post-communist regimes. While being the most definitive book on the topic, the book is nevertheless written in an accessible style suitable for both beginners who wish to understand the logic of post-communism and scholars who are interested in original contributions to comparative regime theory. The book is equipped with QR codes that link to www.postcommunistregimes.com, which contains interactive, 3D supplementary material for teaching.